40 Years of Total Extracorporeal Septal Reconstruction: The Past, Present, and Future. Issue 6 (December 2020) - Gubisch, Wolfgang; Hacker, Stefan; Neumann, Jens; Haack, Sebastian
Abstract : Background: Even today, severe septal deformities are a challenging problem for any rhinoplasty surgeon. Standard techniques are often not able to achieve satisfactory long-term results regarding function or aesthetic form. In such severe cases, a partial or total extracorporeal septal reconstruction may be used, as these techniques provide reliable and lasting results. Methods: The aim of this work is to present the authors' experience with the technique of total extracorporeal septal reconstruction and its development to today's standard and to prove its effectiveness in the long-term follow-up. Results: This article presents 40 years of clinical experience in this field and describes the technical changes that have evolved. Low complication rates, safe techniques, and favorable long-term outcomes of the total extracorporeal septal reconstruction show the benefits of this technique. Conclusion: The indication for a total extracorporeal septal reconstruction has been limited by the development of less complex surgical procedures, but it still represents the best technique to achieve long-term functional and aesthetic results in patients with very complex septal deformities. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, V. Abstract : Supplemental Digital Content is available in the text.